Mathematics Literacy Skill Seen from Learning Style in Discovery Learning Model with Realistic Approach Assisted by Schoology - Madyaratri, Dewi Yanwari; Wardono, Wardono; Kartono, Kartono (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this research is to describe students' mathematics literacy skill seen from learning styles in discovery learning with realistic approach assisted by schoology. This type of research used in this study is mixed methods model of sequential explanatory. The population in this study were VII graders of SMP Negeri 1 Bae. The subject of the research was from VII H of the school. The results showed that the discovery learning model with realistic approach assisted by schoology effective to mathematics literacy skill. Based on the analysis of written test data, observations and interviews, it was found that each type of learning style has different mathematics literacy skill. This is shown from 2 students diverger learning style categories there are 1 high category and 1 poor category, from 8 students assimilator category there are 3 high category, 3 moderate category and 2 poor category, from 9 students the converger category there are 4 high category and 5 moderate category and from 12 students accommodator category there are 1 high category, 5 moderate category and 6 poor category.